2015
DOI: 10.1177/0162643415623026
|View full text |Cite
|
Sign up to set email alerts
|

Student Response Systems

Abstract: This study presents findings from an investigation of student response systems (SRS) in an undergraduate preservice teacher education classroom to investigate the impact of SRS use during lecture on the topic of learning disabilities (LDs). Participants were randomly assigned to the SRS group, a written response group, or a no response group, and evaluated at pre-and posttest for content knowledge, during lecture for reading accountability and engagement, at posttest regarding satisfaction with the learning ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A teacher poses a question or task to his or her students via an overhead or computer projector. Students, on the other hand, provide an appropriate response for the task given using a handheld transmitter or a 'clicker' (Thomas et al, 2015). Technology-backed learning environment like this will trigger an interactive classroom, motivating students to participate and interact with others in the learning process (Fui-Theng & Mai, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A teacher poses a question or task to his or her students via an overhead or computer projector. Students, on the other hand, provide an appropriate response for the task given using a handheld transmitter or a 'clicker' (Thomas et al, 2015). Technology-backed learning environment like this will trigger an interactive classroom, motivating students to participate and interact with others in the learning process (Fui-Theng & Mai, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SRS has been reported by students to be helpful and engaging which is more likely to foster learning. Thomas et al (2015) found students report SRS engaging and helpful to their learning (Thomas, Pinter, Carlisle, & Goran, 2015). The use of engaging instruction or interactions like SRS more actively engage students fostering more student learning.…”
Section: Classroom Engagementmentioning
confidence: 99%